Seven new species of Polystichum (subg. Haplopolystichum; Dryopteridaceae) from southern China - Han, Meng-Qi; Liu, Yan; Zhang, Li-Bing (Phytotaxa, 2016)
Seven new fern species of Polystichum subg. Haplopolystichum (Dryopteridaceae) are described and illustrated from Guizhou and Yunnan provinces, Southwest China. These seven species include P. arcuatum, P. multispinulosum, and P. paucicarpum from Guizhou, and P. crassirachis, P. membranifolium, P. paraobliquum, and P. serratissimum from Yunnan. Four of these seven species are described from limestone caves. All seven species have extremely narrow distributions and are classified as Critically Endangered (CR) following IUCN Red List criteria.